2015
DOI: 10.12693/aphyspola.127.248
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Substituting Quadrivalent Ions Influence on the Properties of La-Sr Manganites

Abstract: Regularities of the inuence of quadrivalent ions and oxygen concentrations on the structural characteristics, saturation magnetization, Curie point, temperature dependence of electrical conductance of ceramic manganites La1−c−xSrc+xMn1−xMe 4+x O3+γ (Me = Ti, Ge; 0.17 ≤ c ≤ 0.35; 0.025 ≤ x ≤ 0.125) were established. The relation between experimental data on lattice parameters, electromagnetic properties and crystal chemistry characteristics (nonstoichiometry index, concentrations of ions residing at dierent cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The unit cell volume (V) of all manganites decreased over time (Table 1). Most considerable decrease of V was observed in the samples with high quantity of titanium, which must reduce overstoichiometric oxygen concentration in sintered manganites [9][10][11]. Variations of diffraction reflexes width during the storage of manganites (Table. 2) were dependent on their composition.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The unit cell volume (V) of all manganites decreased over time (Table 1). Most considerable decrease of V was observed in the samples with high quantity of titanium, which must reduce overstoichiometric oxygen concentration in sintered manganites [9][10][11]. Variations of diffraction reflexes width during the storage of manganites (Table. 2) were dependent on their composition.…”
Section: Resultsmentioning
confidence: 96%
“…x O 3+γ (0.025 ≤ x ≤ 0.150), in which Mn 4+ content is independent of "x". These manganites under synthesis conditions in our experiments have excess oxygen content ( > 0) [9][10][11], and after cooling they are not in a state of thermodynamic equilibrium. The transition into energetically more favorable state is a general cause of the ageing processes.…”
Section: Introductionmentioning
confidence: 84%
“…Space group, unit cell volume (v) of manganites, and the increment of non-stoichiometry index (∆γq after 50 months of storage are presented in Table I. The ∆γ values have been calculated from corresponding data on v decrement using the approach developed in [11]. (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Such conversion may not be directly related to the oxygen absorption, because excess of oxygen content promotes the existence of rhombohedral phase [10]. Actually, after annealing under conditions resulting in stoichiometric oxygen content [8,10,11], this manganite became orthorhombic with v 59.29 Å 3 . The result obtained made it possible to find index γ 0.018 for aged manganite (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the T C decreases significantly in case of 0.85LSMO/0.15GeO 2 composite sample as compared to LSMO and the value is T C = 303 K. It is also observed that, the temperature range of PM-FM transition (defined as the half-width at the half-maximum in dM/dT curve) has almost the same value for both samples ΔT PM-FM ~ 10−15 K. This decrease in T C can be principally a consequence of loss of the ferromagnetic ordering due to incorporation of the nonmagnetic GeO 2 as a secondary phase in the composite sample, but the XRD pattern of 0.85LSMO/0.15GeO 2 does not have any reflections of pure GeO 2 phase. At the same time it is known from the literature that the introducing of tetravalent ions (Ge or Ti) in lanthanum-strontium manganites can lead to the decreasing in the values of the Curie temperature [9][10][11][12]. Change in the Curie temperature for the Bsite substituted manganites mainly originates from two factors: (i) the so-called electronic E-factor: the weakening of the double exchange interaction due to the breaking of the pathway for itinerant e g electrons caused by the difference in electron configurations between the Mn 3+ , Mn 4+ ions and transition metal ions and (ii) the structural S-factor: change of Mn-O bond distances and Mn-O-Mn bond angles because of the difference in Mn and dopant size ionic radii.…”
Section: Magnetization Measurementsmentioning
confidence: 99%